2012
DOI: 10.1016/j.neuroimage.2012.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Task by stimulus interactions in brain responses during Chinese character processing

Abstract: In the visual word recognition literature, it is well understood that various stimulus effects interact with behavioral task. For example, effects of word frequency are exaggerated and effects of spelling-to-sound regularity are reduced in the lexical decision task, relative to reading aloud. Neuroimaging studies of reading often examine effects of task and stimulus properties on brain activity independently, but potential interactions between task demands and stimulus effects have not been extensively explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
1
16
0
1
Order By: Relevance
“…On the other hand, we show here that MFG activity is strongly modulated by task (see also BOOTH, etc.). Analysis of effects of stimulus class [ 19 ] shows that activity in the MFG tracks with behavioral measures of difficulty during LDT. Notably, stimulus effects are not observed in MFG for the same stimuli in a one-back task [ 22 ], which arguably puts an even greater premium on visual processing, but requires less in the way of meta-linguistic decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we show here that MFG activity is strongly modulated by task (see also BOOTH, etc.). Analysis of effects of stimulus class [ 19 ] shows that activity in the MFG tracks with behavioral measures of difficulty during LDT. Notably, stimulus effects are not observed in MFG for the same stimuli in a one-back task [ 22 ], which arguably puts an even greater premium on visual processing, but requires less in the way of meta-linguistic decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…That activity is restricted to the LD task is not surprising, given the insula’s role in error monitoring [ 45 , 46 ], and the language difference may be explained in terms of the lower overall accuracy in the Chinese behavioral data. Yang et al [ 19 ] and Yang & Zevin [ 64 ] further showed that insula activity to conditions with the lowest accuracy in the lexical decision task in both languages. This is a perfect example of a region that behaves very differently under artificial task conditions and naturalistic reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, bottom-up factors have been mainly manipulated by comparing the activation patterns induced by different types of visual input ranging from checkerboards, objects, symbols, sequences of characters, pseudowords to real words (Carreiras et al, 2007;Twomey et al, 2011;Yang et al, 2012). As described below, the present study adopted a different approach that consisted in manipulating the bottom-up information while using only written words, i.e., visual stimuli that can potentially lead to the activation of orthographic, phonological and semantic information.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the neural network of character reading is more uncertain when considering the language differences. Although, pSTG was consistently active for O-P processing in alphabetic word reading ( Paulesu et al, 2000 ), it was null or deactivated for Chinese character either in naming ( Tan et al, 2001a ) or lexical decision (LD) task ( Yang et al, 2012 ), whereas, it was active in Chinese during continuous reading ( Wang et al, 2015 ) and semantic judgment tasks ( Rueckl et al, 2015 ). That is, the task demands might influence the previous findings of the Chinese reading network.…”
Section: Introductionmentioning
confidence: 99%